Analyzing Ash Leaf-Colonizing Fungal Communities for Their Biological Control of Hymenoscyphus fraxineus - Becker, Regina; Ulrich, Kristina; Behrendt, Undine; Kube, Michael; Ulrich, Andreas (Frontiers in Microbiology, 2020)
The invasive ascomycete Hymenoscyphus fraxineus has been threatening Fraxinus excelsior populations throughout Europe for over two decades. Since the infection and first colonisation by the pathogen occurs in leaves, leaf-colonising microorganisms have been discussed as a barrier and as possible biocontrol agents against the disease. To identify fungal groups with health-supporting potential, we compared the fungal microbiota of compound leaves from susceptible and tolerant ash trees in four ash stands with high H. fraxineus exposure. The fungal communities were analysed both culture-independently by ITS2 amplicon sequencing and by the taxonomic classification of 1,704 isolates using matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) or sequencing of the entire ITS region. The fungal community structure did not show significant differences depending on the health status. However, for several OTUs and a MALDI group, a significantly higher abundance was found in tolerant ash trees. Thus, the yeast Papiliotrema flavescens was significantly increased and accounted for 12.3% of the mycobiome of tolerant ashes (OTU0003), and it had also a distinctly higher abundance among the isolates. The filamentous ascomycete Sarocladium strictum was increased 24-fold among the isolates of tolerant trees, but its abundance was comparably low. An in vitro screening for the growth inhibition of the pathogen via cocultivation resulted in 28 yeast-like isolates and 79 filamentous fungi with antagonistic activity. A statistical cocultivation test on two H. fraxineus strains confirmed six of the yeast-like isolates that suppressed H. fraxineus significantly, from 39-50%, two of them through a fungicidal effect. The highest inhibition rates among the yeasts were found for three isolates belonging to Aureobasidium pullulans and P. flavescens. The cocultivation test of the filamentous isolates revealed higher effects compared to the yeasts. Four isolates showed significant inhibition of both H. fraxineus strains with a rate of 72-100%, and five further isolates inhibited only one H. fraxineus strain significantly. The most effective isolates were members of the genus Cladosporium. During the next step, in planta tests will be necessary to verify the efficacy of the antagonistic isolates and to assess their suitability as biocontrol agents.